Optimizing Decentralized Governance: Comparison of Implementation in Indonesia and Malaysia - Nur Syamsudin; Imam Yahya; Kamarul Zaman; Dinda Mauritsa Dina Haq (JPW (Jurnal Politik Walisongo), 2026)
Decentralization has been widely promoted as a strategy to improve governance performance, strengthen local accountability, and improve policy responsiveness. However, its effectiveness depends heavily on the extent to which decentralized governance aligns with institutional structures, sociocultural contexts, and intergovernmental policy dynamics. This study examines how decentralized governance can be optimized by comparing the Province of Central Java in Indonesia and the State of Kedah in Malaysia, which represent two distinct state structures: a unitary system with regional autonomy and a federal system. Using a qualitative comparative case study approach, the study relied on semi-structured interviews with key stakeholders, policy documents, and white papers. Data were analysed using cross-case thematic analysis to identify patterns of convergence and divergence in decentralized practices. The findings suggest that, although decentralization in Central Java grants local governments broader formal authority, it is constrained by institutional capacity and policy coordination challenges. On the other hand, decentralization in Kedah offers greater policy stability but limits local autonomy and innovation due to strong state-level control. The study highlights the importance of aligning central and regional policies, taking into account sociocultural factors, and strengthening participatory mechanisms to optimize decentralized governance. This research contributes to the decentralized literature by emphasizing the need for context-sensitive, adaptive governance models rather than uniform policy designs.